Evaluation of energy generation potential from municipal solid waste in the North-West province, South Africa - Mapereka Francis Chagunda; Tabukeli Musigi Ruhiiga; Lobina Gertrude Palamuleni (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Municipal Solid Waste (MSW) management is rapidly becoming a severe environmental problem worldwide. Developing countries, especially African cities, are the most affected due to inadequate resources to cope with increasing magnitude and complexity of the waste generated as well as the scarcity of land for disposal. As such, strategies which include waste- to-energy (WtE) generation to recover the potent energy from municipal waste could be a better option. This study sought to determine the sustainability of WtE projects for energy access to off-grid residents in the North-West province, South Africa. The study used a quantitative research design coupled with field observations and measurement of elements of the waste chain to generate primary data sets. The information was supplemented by secondary datasets on waste information and waste management at local municipalities. Results revealed that some of the classes of waste have the optimum calorific values and moisture content for WtE. The eligibility of a waste class to be used in WtE generation projects is dependent on the quantities generated. The results also indicate that using paper as fuel in the 240 tonnes/day WtE technology would cover more days of operation than plastics and rubber. Based on the 2020 estimated waste quantities, paper would last 234 days of generating about 6,944 GWh while plastics would last 177 days with energy output of 5, 207 GWh. Waste quantities generated in the North-West province could contribute to sustainable energy access to the off-grid informal settlement residents and advance waste management options through WtE. This study contributes to the literature on renewable energy and waste management in the context of green energy in South Africa.